Cooling rate and storage temperature affect bacterial counts in raw milk - I.M Cox; S. Adapa; Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 1998)
Raw milk was obtained from the K-State Dairy Teaching and Research Center and evaluated for quality after being stored under various conditions. Results showed that as storage temperature increased from 35 to 45EF for 0 to 72 hr, total bacterial counts increased, whereas the titratable acidity and pH values remained fairly constant. Changing the cooling rate affected microbial numbers. Cooling to 40EF within 30 versus 120 min reduced microbial counts by 50%. Finally, the preincubation test was shown to be an effective method to document possible psychrotrophic contamination before the milk arrives at the processing facility.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Raw milk; Cooling rate; Storage temperature; Microbial counts